DETERMINAN PRODUKTIVITAS TENAGA KERJA PADA UMKM BEDETAN IKAN LEMURU DI DESA PERANCAK KABUPATEN JEMBRANA - Widiastuti, Gusti Ayu Ketut; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 6 (2024): Vol.13.No.6. JUNI.2024 [393-451], 2024)
Productivity is the ratio of output to input. Work productivity encompasses an intellectual attitude of a staff member who looks to the future optimistically by holding the confidence that life today is better than yesterday and tomorrow will be better than today. This research was carried out with the aim to analyzing simultaneously and partially the influence of age, motivation, environmental conditions, wages and work experience on labour productivity as well as to know the role of experience in moderating the impact of wages on labor productiveness at Bedetan Lemuru SME in the village of Perancak, Jembrana district. Research design using quantitative with associative design. As for the choice of this location, because the village of Perancak has a huge fishing potential so that there is an innovation to establish Lemuru Dried Fish SME. The population in this study employed 40 workers. Sampling by using saturated sampling. The analytical technique used is moderate regression analysis. The results of the analysis show that at the simultaneously age, motivation, environmental conditions, wages and work experience have a significant effect on labour productivity. Partially age, motivation, environmental conditions and work experience have a significant positive effect while wages have not significant effect on labour productivity. Experience moderates the impact of wages on labour productivity. Age has a dominant influence on labour productivity. Keywords:     Age,    Motivation,    Environmental    Conditions,     Wages,     Experience, Labor Productivity, Bedetan Perancak SME, Jembrana Ragency.